Evaluasi Kelayakan Kapasitas Drainase Pada Jalan Perumahan Arcawinangun, Kecamatan Purwokerto Timur, Kabupaten Banyumas - Raditya Rahadian Anggara; Iskahar (Proceedings Series on Physical & Formal Sciences, 2026)
Drainage on Arcawinangun Housing Road, East Purwokerto Subdistrict, Banyumas Regency often experiences flooding caused by sedimentation. This study aims to determine the drainage capacity on Arcawinangun Housing Road, East Purwokerto Subdistrict, Banyumas Regency, whether it is still capable of accommodating and draining the total flow of rainwater runoff and household waste. The results of the study and calculations show that the total flow (Qtotal) ranges from 0.00361 m³/sec to 0.01086 m³/sec and the existing drainage channel flow after sedimentation (Qsed) ranges from 0.065 m³/sec to 2.488 m³/sec. The conclusion of this study is that the discharge of existing drainage channels after sedimentation is greater than the total flow discharge (Qsed > Qtotal), meaning that each existing drainage channel after sedimentation is still capable of accommodating and draining the total flow discharge of both rainwater runoff and household waste. .